The Impact of Gadget Use on the Decrease in Students' Physical Activity in Everyday Life - Suci Nurhafifah; Aam Ali Rahman; Dinar Dinangsit (Universitas Negeri Semarang, 2026)
Digital technology advancement has led to increased gadget usage among elementary school students but their extended screen time and high screen exposure risks transforming their daily activities from active play to sedentary behavior. The research investigates how students' physical activities change when they spend more time using gadgets during their daily routines. The research employed explanatory case study qualitative methods to gather data through structured interviews and direct observations of six students who spent most of their time using gadgets. The research demonstrates that students use gadgets mainly for watching content which creates three main obstacles to their physical activity: decreased motivation and physical abilities and reduced involvement in unstructured physical activities. Students maintain their participation in Physical Education (PE) activities but they now choose to spend their free time watching screens instead of being active. The research demonstrates that the length of time students spend with gadgets determines which activities they perform throughout their day. The research findings help parents and educators and policymakers create effective digital monitoring systems and enhance physical activity opportunities to support children's healthy development in today's digital world.